Collection Development in Indian Academic Libraries: An Empirical Approach to Determine the Number of Copies for Acquisition - Giri, Rabishankar; Sen, B. K.; Mahesh, G. (DESIDOC Journal of Library & Information Technology, 2015)
Collection development in academic libraries has many challenges and one of them concerns determining the number of copies of some books that are required in multiple copies in the library. In the present study, five major academic libraries in New Delhi were surveyed to understand the prevalent policies and practices on determining the number of copies of books that are required in multiple copies. It was found that there was no consistency in the approach to deciding the number of copies in the libraries studied. Further it was noted that all the libraries arbitrarily decided on the number of copies to be purchased. The paper discusses a method that has been evolved to determine the number of copies. The method has been applied in one of the academic libraries under study which when combined with other measures have been found to be more effective in determining the number of copies required.